Hollow micro-/nanostructures : synthesis and applications - Lou, David Xiong Wen (2012)
Hollow micro-/nanostructures are of great interest in many current and emerging areas of technology. Perhaps the best-known example of the former is the use of fly-ash hollow particles generated from coal power plants as partial replacement for Portland cement, to produce concrete with enhanced strength and durability. This review is devoted to the progress made in the last decade in synthesis and applications of hollow micro-/nanostructures. We present a comprehensive overview of synthetic strategies for hollow structures. These strategies are broadly categorized into four themes, which include well-established approaches, such as conventional hard-templating and soft-templating methods, as well as newly emerging methods based on sacrificial templating and template-free synthesis. Success in each has inspired multiple variations that continue to drive the rapid evolution of the field. The Review therefore focuses on the fundamentals of each process, pointing out advantages and disadvantages where appropriate. Strategies for generating more complex hollow structures, such as rattle-type and nonspherical hollow structures, are also discussed. Applications of hollow structures in lithium batteries, catalysis and sensing, and biomedical applications are reviewed.